Utilização de uma plataforma sig para a concepção de rotas de transporte coletivo - Orozco, David Javier Julio (2014)
Transport is the main factor of development of a region, for this reason, the aim of securing efficient mobility in the urban area becomes ever more important for transport and traffic agencies, who base the planning of transportation systems in the analysis of data relating to the supply of services and their demand, being necessary to characterize the offer based on a set covering as much data as posible about the urban infrastructure and transport networks with their respective operational characteristics making necessary an evolution of the tools for the management and development of solutions able to identify , analyze and to the extent possible, resolve the many problems caused by different types of agents which influence the urban centers making inefficient the urban transport systems and generating environmental degradation, reduction of the built heritage, as well as changes in the structure of land use. The overall objective of this work is get from a methodology based on a Geographic Information System the reinterpretation of a planning model for the estimating demands of mobility, being evaluated different scenarios of urban and enviromental mobility of Passo Fundo city in order to support and guide the decisions making processes on local transport, creating a way to improve decision making in municipal management, and planning of system of public Transportation - STP by bus